Elemental systematics of the calcitic skeleton of Corallium rubrum and implications for the Mg/Ca temperature proxy - Chaabane, S.; López Correa, Matthias; Ziveri, P.; Trotter, J.; Kallel, N.; Douville, E.; McCulloch, M.; Taviani, M.; Linares, C.; Montagna, P. (Chemical Geology, 2019)
The high-Mg calcite skeleton of Corallium rubrum was analyzed from living colonies collected from a wide range of depths (15 m to 607 m) and environmental settings in the Mediterranean Sea. An overarching goal was to better understand the calcification process and incorporation of elements into the slow-growing skeleton of both shallow and deep-water specimens, and more specifically, to clarify the veracity of geochemical proxies for reconstructing seawater temperatures. The coral internal structure including growth bands were determined by scanning electronic microscopy (SEM) and petrographic techniques. Trace elements (Li, B, Mg, Sr and Ba) compositions of the coral skeleton were obtained by solution and laser ablation inductively coupled plasma mass spectrometry (ICP-MS). Results show that the skeleton of the deep-water specimens has an internal microstructure similar to shallow-water colonies, with the medullar and the annular zones clearly distinguishable in both shallow and deep-water specimens. In general, the bands of the deep-water samples are very thin and equidistant compared to the irregular banding of the shallow-water specimens. Banding differences relate to the contrasting environmental dynamics, with the shallow-water specimens being exposed to large seasonal fluctuations compared to the relative stable conditions of those inhabiting bathyal depths. The inner medullar and outer annular portions differ in their trace element concentrations: Mg/Ca, Sr/Ca and Li/Ca ratios are higher in the medullar zone and seem to be influenced by growth kinetics, whereas B/Ca and Ba/Ca are similar in both zones and hence unaffected by growth rate. The variability of elemental ratios is lower in the deep-water specimens. Growth bands are highly correlated to Mg/Ca, Sr/Ca and Li/Ca, suggesting common mechanism(s) controlling the incorporation of these elements into the coral skeleton. Mg/Ca ratios were especially depleted in the dark bands. Although the mean Mg/Ca of each specimen is positively correlated to ambient seawater temperature, the intra-annual variations and amplitudes differ and do not correlate to the band widths. These findings suggest that intra- and inter-annual variations of Mg/Ca cannot be used to reconstruct a continuous time-series of long-term seasonal temperature records. However, the mean Mg/Ca composition can serve as a valuable proxy to estimate mean palaeoseawater temperature at a given site within the Mediterranean.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Calcite skeleton; Corallium rubrum; Growth bands; Mediterranean Sea; Red coral; Temperature proxy; Trace elements